The Application of molecular Biology in the development of Strptomycete systematics - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT: The application of molecular biology in the field of microbial systematics has been viewed as the renaissance period in unraveling microbial diversity. The most substantial change in microbial sytematics which has brought about by the application of molecular approach is the revolution in basic view of microbial diversity, especially the introduction of species concept based on molecular data. As a result, genomic species concept has been proposed on well defined and universally applicable criteria, notably the estimation of the genetic relatedness between organisms by measuring the degree of homology between their DNA molecules. Consequently, streptomycete systematics has experienced a dramatic change in terms of phylogenetic classification and molecular fingerprinting due to extensive practice of molecular methods. This paper will review the impact of the studies on nucleic acid sequencing and fingerprinting as well as DNA: DNA relatedness on the current status of the streptomycete systematics which is the basic tools to unravel streptomycete diversity in natural habitats.